2019
DOI: 10.1002/brb3.1454
|View full text |Cite
|
Sign up to set email alerts
|

Single‐center study of autoimmune encephalitis‐related autoantibody testing in Hungary

Abstract: ObjectiveAutoantibody detection is crucial for the early diagnosis of autoimmune encephalitis (AIE) since prompt therapy can determine the disease outcome. Here, we report a single‐center 6‐year retrospective study of autoantibody testing in AIE in the Hungarian population.MethodsSerum and/or cerebrospinal fluid (CSF) autoantibody tests were performed using cell‐based indirect immunofluorescence assay for AIE diagnosis. Samples were provided by neurology clinics as part of a nationwide program. Test results we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
3
6
0
Order By: Relevance
“…In our study, due to the low number of pediatric cases with age < 10 years (four cases), we could not confidently determine characteristics of pediatric patients. Although, the study has modest sample size, it summarizes detailed clinical data of 35 neuronal surface antibody positive patients from the 60 patients with positive autoantibody test results (N total = 1,034 patients with suspected AE) from 2012 through 2018 in Hungary published in our previous study (10). Our data confirms results of previous publications and further clarifies clinical data of AE patients with neuronal cell surface autoantibodies.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In our study, due to the low number of pediatric cases with age < 10 years (four cases), we could not confidently determine characteristics of pediatric patients. Although, the study has modest sample size, it summarizes detailed clinical data of 35 neuronal surface antibody positive patients from the 60 patients with positive autoantibody test results (N total = 1,034 patients with suspected AE) from 2012 through 2018 in Hungary published in our previous study (10). Our data confirms results of previous publications and further clarifies clinical data of AE patients with neuronal cell surface autoantibodies.…”
Section: Discussionsupporting
confidence: 86%
“…The study by Bien et al ( 21 ) reported 576 antibody-positive patients during testing of 10,919 patients for a broad panel of neural antibodies, including onconeural and neuronal cell surface autoantibodies. Our previous study ( 10 ) included results of 60 neuronal cell surface autoantibody positive patients (anti-NMDAR, anti-LGI1, anti-GABABR, anti-Caspr2, anti-AMPAR1, 2) and our recent study exclusively included both serologically (neuronal cell surface antibody positive, but not onconeural autoantibody positive) and clinically positive definite AE patients. The distinct results in autoantibody frequencies detected in the two laboratories, may be due to the exclusive inclusion of neuronal cell surface autoantibody positive AE patients in our study, making it impossible to compare accurately the data of autoantibody frequencies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, antineuronal autoantibodies were detected in 8 (4%) out of 200 patients with a clinical diagnosis of encephalitis, which is similar to the proportion reported for the United States (4.2%; based on anti-NMDAR) [ 38 ] and only slightly lower than that reported for Hungary (5.8%; based on anti-NMDAR, anti-LGI1, anti-Caspr2, anti-GABABR, anti-AMPAR1, and anti-AMPAR2) [ 39 ] and the United Kingdom (7.9%; based on anti-VGKC and anti-NMDAR) [ 40 ]. In our study, the vast majority of detected autoantibodies were anti-NMDR (87.5%), which is compatible with other reports; for example, in the study by Saraya et al [ 41 ], anti-NMDAR antibodies were present in 81% of AE cases with detectable neuronal surface antibodies.…”
Section: Discussionsupporting
confidence: 76%